The Efficacy of a Virtual Reality Exposure Therapy Treatment for Fear of Flying: A Retrospective Study - Gottlieb, Amihai; Doniger, Glen M.; Hussein, Yara; Noy, Shlomo; Plotnik, Meir (Frontiers in Psychology, 2021)
Background: Fear of flying (FoF) is a phobia with 10–40% prevalence in the industrialized world. FoF is accompanied by severe economic, social, vocational, and emotional consequences. In recent years, virtual reality (VR)-based exposure therapy (VRET) for FoF has been introduced. Positive long-term efficacy of FoF-VRET has been reported by several studies, which, however, were limited by relatively small, non-representative samples and a lack of comparative pre/post functional efficacy outcome measures. Our objective was to evaluate the efficacy of a VRET treatment utilizing a large-scale VR system, experienced by a representative sample of self-referred individuals. Methods: We conducted a retrospective survey. Of 274 individuals who received the treatment (over a period of three years), 209 met inclusion/criteria, and 98 agreed to participate. We mainly collected information regarding flight activity before and after treatment relying on evidence such as boarding passes and flight tickets. The primary outcome measures were: (1) number of flights per month (FpM); (2) number of flight hours per month (FHpM). For each participant, these outcomes were computed for the post-treatment period (≥6 months after FoF-VRET) and the corresponding pre-treatment period. Results: FpM (mean±SD) increased from .04±.06 to .16±.14flights (p<.0001). FHpM rose from .19.±.35 to .79±.87 hours per month (p<.0001). Conclusions: These results are indicative of FoF-VRET treatment efficacy. Future studies should evaluate long-term maintenance of the treatment effect and thus identify the optimal frequency for delivery of periodic booster treatments.